PERAN RAHMAH EL YUNUSIYAH DALAM PENDIDIKAN - Latifah Zahra Rahmadhani; Ria Yogi Destiana; Ummi Fadhilah (CV. ADIBA ASIHA AMIRA, 2024)
Rahmah El Yunusiyah is an important figure in Islamic education in Indonesia, especially for women. Through the establishment of Diniyyah Putri, she introduced the concept of education that combines religious and general knowledge, emphasizing equal educational rights between men and women. This research aims to examine in depth Rahmah El Yunusiyah's role in developing women's education. The method used in this research is a qualitative approach using library research. All data used comes from various written sources such as books, documents, and manuscripts. The results showed that Rahmah El Yunusiyah's role in education was enormous. By combining religious and general education, Rahmah succeeded in creating a complete and inclusive education system for women. The educational institution she founded, Diniyyah Putri, has had a major impact in increasing women's access to formal education. In conclusion, Rahmah el Yunusiyah has made major changes in education, especially for women. Her contributions created a strong foundation for women's education in Indonesia. By combining religious and general education, and fighting for equal educational rights between men and women, Rahmah succeeded in having a positive impact on educators today to continue to support equitable and thriving education for all.